DECREASE OF FRICTIONAL SPARK FORMATION OF STEEL ARTICLES BY MEANS OF THE CHEMICAL HEAT TREATMENT PROCESSES - A. A. Bakinovskij (Литьë и металлургия)
The influence of the structure and properties of diffusion-alloys layers to the level of sparking in frictional contact. Demonstrated a special installation for testing materials and coatings for intrinsic safety. Show the results of boron-containing diffusion layers of the intrinsic safety.